Group of women sitting in the woods listening to a woman at a podium - Unknown:::Creator::::::::::::
Photograph shows a group of women sitting on benches in the woods listening to a woman at a podium. Their backs are to the camera. There is one woman sitting in the background on the right side facing the camera. They are probably at the YWCA's Camp Ayun Mapu in Big Basin, California.